Genome-wide association mapping of lentil (Lens culinaris Medikus) prebiotic carbohydrates toward improved human health and crop stress tolerance - Nathan Johnson (Nature Portfolio, 2021)
Abstract Lentil, a cool-season food legume, is rich in protein and micronutrients with a range of prebiotic carbohydrates, such as raffinose-family oligosaccharides (RFOs), fructooligosaccharides (FOSs), sugar alcohols (SAs), and resistant starch (RS), which contribute to lentil's health benefits. Beneficial microorganisms ferment prebiotic carbohydrates in the colon, which impart health benefits to the consumer. In addition, these carbohydrates are vital to lentil plant health associated with carbon transport, storage, and abiotic stress tolerance. Thus, lentil prebiotic carbohydrates are a potential nutritional breeding target for increasing crop resilience to climate change with increased global nutritional security. This study phenotyped a total of 143 accessions for prebiotic carbohydrates. A genome-wide association study (GWAS) was then performed to identify associated variants and neighboring candidate genes. All carbohydrates analyzed had broad-sense heritability estimates (H 2) ranging from 0.22 to 0.44, comparable to those reported in the literature. Concentration ranges corresponded to percent recommended daily allowances of 2–9% SAs, 7–31% RFOs, 51–111% RS, and 57–116% total prebiotic carbohydrates. Significant SNPs and associated genes were identified for numerous traits, including a galactosyltransferase (Lcu.2RBY.1g019390) known to aid in RFO synthesis. Further studies in multiple field locations are necessary. Yet, these findings suggest the potential for molecular-assisted breeding for prebiotic carbohydrates in lentil to support human health and crop resilience to increase global food security.